2019
DOI: 10.2147/vhrm.s204097
|View full text |Cite
|
Sign up to set email alerts
|

<p>Periodontitis As A Risk Factor For Stroke: A Systematic Review And Meta-Analysis</p>

Abstract: This systematic review and meta-analysis investigate the association between periodontitis and stroke. This review followed the methods established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Searches were conducted in five databases and two sources of grey literature. After the selection of the articles, a risk of bias evaluation was performed. Three meta-analyzes were performed: Assessing the overall association between stroke and periodontitis in case–contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 62 publications
2
48
0
4
Order By: Relevance
“…Observational studies have associated periodontitis with a range of diseases, including cardiovascular disease [ 5 ], Alzheimer's disease [ 13 ], hypertension [ 14 ], and diabetes [ 15 ]. A recent meta-analysis found that individuals with periodontitis had almost two-fold greater risk of stroke, with this effect further pronounced for events of ischaemic origin [ 16 ]. However, observational studies are subject to confounding; for example, those with periodontal disease may have poorer access to healthcare or lower income [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have associated periodontitis with a range of diseases, including cardiovascular disease [ 5 ], Alzheimer's disease [ 13 ], hypertension [ 14 ], and diabetes [ 15 ]. A recent meta-analysis found that individuals with periodontitis had almost two-fold greater risk of stroke, with this effect further pronounced for events of ischaemic origin [ 16 ]. However, observational studies are subject to confounding; for example, those with periodontal disease may have poorer access to healthcare or lower income [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent meta-analyses, authors compared oral health between stroke patients and controls (healthy population). The results indicated that stroke patients had poorer oral health and worse periodontal status [ 8 , 9 , 10 ] as well as less frequent dental attendance behavior than controls [ 11 , 12 ]. Therefore, further research concerning oral health problems after stroke should be conducted, and effective management strategies need to be devised and implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is the main cause of tooth loss in middle aged and older adults [11]. In previous studies, increased number of tooth loss caused by chronic inflammation due to gingivitis and periodontitis was related to cardiovascular diseases including myocardial infarction, stroke, and long-term mortalities [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%